An in silico derived dosage and administration guide for effective thermochemical ablation of biological tissues with simultaneous injection of acid and base. (December 2022) - Mak, Nguoy L.; Ooi, Ean H.; Lau, Ee V.; Ooi, Ean T.; Pamidi, Narendra; Foo, Ji J.; Mohd Ali, Ahmad F.
Highlights: A TCA framework for simultaneous infusion of acid and base was developed. Effects of infusion rate, reagent concentration, volume and type were examined. A 7.5 M reagent concentration is optimum for treatment safety and efficacy. Coagulation volume achieved is always greater than the reagent volume infused. Equations were derived to help clinicians select proper treatment parameters. Graphical abstract: Abstract: Background and objectives: Thermochemical ablation (TCA) is a thermal ablation technique involving the injection of acid and base, either sequentially or simultaneously, into the target tissue. TCA remains at the conceptual stage with existing studies unable to provide recommendations on the optimum injection rate, and reagent concentration and volume. Limitations in current experimental methodology have prevented proper elucidation of the thermochemical processes inside the tissue during TCA. Nevertheless, the computational TCA framework developed recently by Mak et al. [Mak et al., Computers in Biology and Medicine, 2022, 145:105494] has opened new avenues in the development of TCA. Specifically, a recommended safe dosage is imperative in driving TCA research beyond the conceptual stage. Methods: The aforesaid computational TCA framework for sequential injection was applied and adapted to simulate TCA with simultaneous injection of acid and base at equimolar and equivolume. The developed framework, which describes the flow of acid and base, their neutralisation, the rise in tissue temperature and the formation of thermal damage, was solved numerically using the finite element method. The framework will be used to investigate the effects of injection rate, reagent concentration, volume and type (weak/strong acid-base combination) on temperature rise and thermal coagulation formation. Results: A higher injection rate resulted in higher temperature rise and larger thermal coagulation. Reagent concentration of 7500 mol/m 3 was found to be optimum in producing considerable thermal coagulation without the risk of tissue overheating. Thermal coagulation volume was found to be consistently larger than the total volume of acid and base injected into the tissue, which is beneficial as it reduces the risk of chemical burn injury. Three multivariate second-order polynomials that express the targeted coagulation volume as functions of injection rate and reagent volume, for the weak-weak, weak-strong and strong-strong acid-base combinations were also derived based on the simulated data. Conclusions: A guideline for a safe and effective implementation of TCA with simultaneous injection of acid and base was recommended based on the numerical results of the computational model developed. The guideline correlates the coagulation volume with the reagent volume and injection rate, and may be used by clinicians in determining the safe dosage of reagents and optimum injection rate to achieve a desired thermal coagulation volume during TCA.